Tackling misunderstandings: A farmer-led approach to improve the usability of multi-decadal climate services - Stephen Snow; Aysha Fleming; Yuwan Malakar; Emma Jakku; Simon Fielke; Rebecca Darbyshire; Graham Bonnett (Climate Services, 2025)
Future climate projections are incorporated into a growing number of interactive online platforms, changing the way users interact with climate information. Motivated by user-centred research, this paper bridges the micro-level considerations of interface design, usability, comprehension and interpretation with more macro-level interaction design concerns, including adoption. We examine users’ understanding and navigation of short-term weather websites relative to longer-term climate projections. Focusing on farmers’ first impressions of a multi-decadal climate service, called My Climate View, we detail how they used and interpreted the interface and highlight where misunderstandings occurred. Our findings show how: (a) Users’ experience of climate projections are shaped by past experiences, including local knowledge and weather knowledge. (b) Misunderstandings of data, although uncommon, can severely undermine perceived usefulness and trust and can occur despite users reporting satisfactory interface usability. These findings underscore how usability and comprehension research can extend broader social science work on technology acceptance, behaviour and social connections. We provide suggestions for the design of online multi-decadal climate services that seek to maximise usefulness and usability and minimise misunderstandings of the information they provide.